Khảo sát các yếu tố ảnh hưởng đến kích thước hạt oxit niken được điều chế bằng quá trình tự bốc cháy gel - Đại, Lưu Minh; Nhiệm, Đào Ngọc; Ninh, Vũ Thế; Chức, Phạm Ngọc (Vietnam Journal of Chemistry, 2014)
Nickel oxide with tiny particle sizes is formed by auto combustion process of nickel nitrates and polyvinyl alcohol (PVA) gel. Factors affecting on particle sizes of nickel oxide including pH and temperature of gel formation, mole ratio of concentration of nickel and the concentration of polyvinyl alcohol used to produce gel were examined. The particle size distribution of nickel oxide was measured by particles analyzer. The powders morphology was observed by Transmission Electron Microscopy (TEM).